Public Preferences for Land uses' changes - valuing urban regeneration projects at the Venice Arsenale - Patrizia Riganti; Anna Alberini; Alberto Longo (European Regional Science Association (ERSA), 2005)
This paper discusses the results of a conjoint analysis study developed to assess alternative land uses for an important part of the city of Venice: its Arsenal. Aim of the study is to illustrate the potential of stated preferences techniques for placing a value on redevelopment and reuse alternatives for an underutilized site with high historical, cultural and architectural significance. Very few studies have used conjoint choice to assess public preferences for alternative land uses in an ex-ante framework, i.e. masterplans. For our study, we wanted to concentrate on a "city of art,” where the relationship between cultural heritage resources management and city development is more critical. Venice was an obvious choice for the national and international relevance of its heritage. The Arsenale is one of the few places in Venice that has the potential for a real transformation of its uses, with important impacts on both residents and visitors. Moreover, the Arsenale plays a strong symbolic role: it was the place where the strength and power of the Serenissima was built. The City Council of Venice has recently deliberated that the Arsenale is an inalienable heritage of the city of Venice. In recent years, the importance of the Arsenale has resulted in a heated debate on its possible new uses. Many architectural proposals have been submitted through international competitions. These proposals—whether submitted in the past or currently under consideration—have shown that there may be a conflict between different possible land uses and the transformation allowed by the existing architectural structures. We surveyed individuals in Venice asking respondents to engage in conjoint choice tasks, gathering 168 usable observations. Members of the general public were intercepted at the Multimedia Library at Palazzo Querini Stampalia/FEEM and asked to indicate which choice they preferrd among hypothetical—but realistic—redevelopment projects of the Arsenale historic site. Each project was described by a vector of attributes, such as land use, use of basins and waterways, architectural features, access, employment implied by the reuse, and cost. The responses to these choice tasks was used to infer the rate at which respondents trade off land uses, aesthetic features, and costs, and hence to derive the value of marginal changes in the attributes, and the value of a proposed policy package. The Venice Arsenale is owned by the Italian government and is currently used by the Italian Navy. The Arsenale site accounts for about 15 percent of the area of the city of Venice (about 45 hectares), and is located in the Castello district. Tradition has it that doge Ordefalo Falier founded the Arsenale—a shipbuilding yard—in 1104. In 1340 the "Darsena Nuova” was created, which marked the birth of the Arsenal Nuovo and of the Corderie building. Further expansion started in 1473, covering an area of 26 hectares. This phase lasted more than 100 years, resulting in the construction of the New Corderie building, among others, in 1591. In its heyday, the Arsenale employed roughly 20,000 workers in an assembly-line fashion and produced one ship a day. The Arsenale, after the navy largely withdrew from the complex over 40 years ago, suffered from abandonment and under use. The Arsenale is, therefore, one of the few places in Venice that has the potential for a real transformation of its uses. In this paper we investigate how the development of the Arsenale site, involving alternative land uses, may influence the welfare of the residents of the historical city center of Venice. Starting from the evidence of our survey in Venice, the paper broaden its scope to discuss ways of improving the management of cultural heritage cities, focusing on new forms of involvement and public participation based on public preferences' elicitation. We debate the issues related to city governance and the need for an appropriate level of democratic participation. An integrated approach, capable of bridging the practice of economic valuation, urban design, conservation of the built environment, and decision-making support systems is here analysed.
Keywords: 330